Class 7 Math Solution WBBSE Algebra Chapter 6 Factorisation Exercise 6 Solved Problems
1. Factorisation of an algebraic expression is the process of finding two or more expressions whose product is the given expression.
⇒ These two or more expressions are called factors.
⇒ Factors of 6 are 1, 2, 3 and 6 [6 = 1 x 6 = 2 x 3]
⇒ The prime factors of 6 are 2, 3
2. Every number or expression is a factor of itself and 1 is a factor of any number or expression.
3. Generally 1 and the number itself may not be written to mention the factors of a number. The factors of 3ab is 3, a, and b where 3, a, and b are prime factors.
⇒ As 6x2y= 2 x 3 x x x x x y
Read and Learn More WBBSE Solutions for Class 7 Maths
Common factor: An expression that can divide all the terms of a polynomial is called the common factor of the polynomial.
Example: 4x3– 12x + 16x
= 4x x x2 – 4x x 3 + 4x x 4
= 4x (x2 – 3 + 4)
Here 4x is the common factor.
Method of factorization:
1. Dividing all the terms of the expression by the largest common factor which is written outside a bracket and putting the resulting quotient inside the bracket.
2.As we arrange the terms of the given algebraic expression in groups such that each group has a common factor. Then we factorise each group separately we take out factors which is common to each group.
3. If any expression is the difference of the square of two expressions, its factors will be the sum of those two expressions and their difference.
i.e., an expression of the form a2– b2 can be expressed as the product of (a + b) and (a – b).
4. Some expressions which are not in the form a2 – b2, can be expressed as the difference of two squares by adding or subtracting some quantity to or from those expressions.
Wbbse Class 7 Maths Solutions
Question 1. Choose the correct answer
1. The number of prime factors of 9x2y is
1. 2
2. 3
3. 4
4. 5
Solution: 9x2y= 3 x 3 x x x x x y
The number of prime factors of 9x2y is 5
⇒ So the correct answer is 4. 5
2. The common factor of 14ab2 and 21ab is
1. 7ab
2. 7a
3. 7b
4. 7ab2
Solution: 14ab2 = 2 x 7 x a x b x b
21 ab = 3 x 7 x a x b
The common factor of 14ab2 and 21ab is (7 x a x b) or 7ab
⇒ So the correct answer is 1. 7ab
3. The sum of factors of (2x – 6) is
1. 2x-5
2. x – 1
3. x – 3
4. x-8
Solution: 2x – 6
= 2(x-3)
Sum of factors is 2 + x – 3 = x – 1
⇒ So the correct answer is 2. x – 1
4. If two factors of a expression are (x + 1) and (x 1), then the expression is
1. 2x
2. 2
3. x2-1
4. None of these
Solution: The expression is (x + 1)(x − 1) = x2– 1
⇒ So the correct answer is 3. x2-1
Wbbse Class 7 Maths Solutions
Question 2. Write ‘true’ or ‘false’
1. The common factor of 10x2y and 15xy2 is 5xy
Solution: 10x2y=2 x 5 x x x x x y
15xy2 =3 x 5 x x x y x y
The common factor is (5 x x x y) or 5xy
⇒ So the statement is true.
2. The sum of factors of (a3-a2+ a) is (a2 + 1)
Solution: a3 – a2 + a = a (a2 – a + 1)
The sum of factors = a2 +1 = a2 + 1
⇒ So the statement is true.
3. Sum of factors of (3a2 – 12a) is (4a + 4).
Solution: 3a2 – 12a = 3a(a – 4)
Sum of factors= 3+a+a-4 = 2a – 1
⇒ So the statement is false.
Wbbse Class 7 Maths Solutions
Question 3. Fill in the blanks
1. The common factor of 18x2, 27x3 and 45x is _____
Solution:
18x2 = 2 x 3 x 3 x x x x
27x3 = 3 x 3 x 3 x x x x x x
45x = 3 x 3 x 5 x x
⇒ The common factor is (3 x 3 x x) or 9x.
2. The sum of factors of (ax + bx- ay- by) is
Solution: ax + bx – ay – by
= x (a + b) -y (a + b)
=(a+b) (x-y)
⇒ Sum of factors = a+b+x-y.
3. The factors of (ab – 5b + a – 5) are ____
Solution: ab – 5b + a – 5
= b(a – 5) + 1(a-5)
= (a – 5)(b + 1)
⇒ The factors are (a – 5) and (b + 1).
Question 4. Find the number of prime factors of a(x2 – y2).
Solution: a(x2– y2) = a(x + y)(x − y)
The prime factors are a, (x + y), and (x − y).
∴ The number of prime factor is 3.
Question 5. Find the sum of factors of (a3 – a).
Solution: a3 – a
= a(a2 – 1)
= a(a + 1)(a− 1)
⇒ Sum of factors = a + a + 1+ a -1 = 3a
Wbbse Class 7 Maths Solutions
Question 6. Resolve into factors
1. a2 – 1 + 2b – b2
2. x2– 2x – y2+ 2y
3. 81x4+4y4
4. 3x4 + 2x2y2– y4
5. a4 + a2b2 + b4
6. \(a^2+\frac{1}{a^2}+1\)
7. xy(1 + z2) +z (x2 +y2)
8. a2 – 5a+6
9. 2a2b2+2b2c2 + 2c2a2-a4-b4-c4
10. x2 + 2x – 899
Solution:
1. a2 – 1 + 2b – b2
2. x2– 2x – y2+ 2y
3. 81x4+4y4
4. 3x4 + 2x2y2– y4
5. a4 + a2b2 + b4
6. \(a^2+\frac{1}{a^2}+1\)
7. xy(1 + z2) +z (x2 +y2)
8. a2 – 5a+6
9. 2a2b2+2b2c2 + 2c2a2-a4-b4-c4
10. x2 + 2x – 899
Wbbse Class 7 Maths Solutions
Question 7. Factorise the following
1. (a + b)4+ 4
2. a2(b-c)2-b2(c – a)2
3. 64ap2– 49a (p- 2q)2
4. a2 – b2 -6ap + 2bp + 8p2
5. 4a4 + 11a2 + 25
Solution:
1. (a + b)4+ 4
2. a2(b-c)2-b2(c – a)2
3. 64ap2– 49a (p- 2q)2
4. a2 – b2 -6ap + 2bp + 8p2
5. 4a4 + 11a2 + 25
Factorisation
Factorisation Exercise 6.1
Let us factorize the following :
1. 25xy = 5 × 5 × x × y
2. 18 × y2 = 2 × 3 × 3 × x × y × y
3. 15q2r2= 3 × 5 × q × q× r × r
4. 10 × yz = 2 × 5 × x × y × z
5. 12 × yz = 2 × 2 × 3× x × y × z
Factorisation Exercise 6.2
Let us factorize the following :
1. 12x2y (x + 2)= 2 × 2 × 3 × x × x × y × (x + 2)
2. 1 8yz2 (2y + 3z) = 2 × 3 × 3 × y × z × z × (2y + 3z)
3. 1 6 × yz (x + y)= 2 × 2 × 2×2 × x × y × z × (× + y)
4. 15pq2 (p + 3q) = 3 × 5 × p × q × q × (p + 3q)
5. 14mn2 (2m – n) = 2 × 7 × m × n × n × (2m-n)
Question 1. Let us factorize:
1. 2+14x
Solution:
2+14x = 2(1 +7x)
2. 5x – 20y
Solution:
5x – 20y = 5 ( x- 4y)
3. 6x – 3y
Solution:
6x – 3y = 3 (2x – y)
4. 3a2 – 12a
Solution:
3a2 – 12a = 3a (a -4)
Question 2. Let us find the common factors of the following algebraic expressions.
1. 6a, 2a2
Solution:
6a, 2a2= 2, a, 2a:
2. 5x, 6xy
Solution:
5x, 6xy = x
3. 4xyz, 12yz
Solution:
4xyz, 12yz = 2, 4, yz, yz, 2y, 2z, 4y, 4z, 4yz.
4. 7a2b, 14abc
Solution:
7a2b, 14abc = 7, a, b, 7a, 7b, ab, 7ab
Class 7 Math Solution WBBSE
Factorization Exercise 6.3
Question 1. Let us Factorise the following
1. xy + y + 3x + 3
Solution:
Given
xy + y + 3x + 3
xy + y + 3x + 3= y (x +1 ) + 3 (× + 1 )
= (x + 1 )(y + 3)
xy + y + 3x + 3 = (x + 1 )(y + 3)
2. pq – q + 2q – 2
Solution:
Given
pq – q + 2q – 2
pq – q + 2q – 2 = q (P – 1 ) + 2 (p – 1 )
= (p – 1 ) (q + 2)
pq – q + 2q – 2 = (p – 1 ) (q + 2)
3. 6xy + 3y + 4× + 2
Solution:
Given
6xy + 3y + 4x + 2
6xy + 3y + 4x + 2 = 3y (2x + 1) + 2 (2x + 1)
= (2x +1) (3y + 2)
6xy + 3y + 4x + 2 = (2x +1) (3y + 2)
4. 10xy + 2y + 5x + 1
Solution:
Given
10xy + 2y + 5x + 1
10xy + 2y + 5x + 1 = 2y (5x + 1 ) + 1 (5x + 1 )
= (5x + 1 ) (2y + 1 )
10xy + 2y + 5x + 1 = (5x + 1 ) (2y + 1 )
Question 2. Let us find the factors of the following algebraic expressions :
1. 7xy
Solution:
7xy = 7 × x × y
2. 9 x2y
Solution:
9 x2y= 3 × 3 × x × x ×y
3. 16ab2c
Solution:
16ab2c = 2 × 2 × 2 × 2 × a × b × b × c
4. -25lmn = 5 × 5 × | × m × n
Solution:
-25lmn = 5 × 5 × | × m × n
5. 12x (2 + x)
Solution:
12x (2 + x) = 2 × 2 × 3 × a × (2 + x )
6. – 5 pq (p2 + 8)
Solution:
– 5 pq (p2 + 8) = -5 × p × q × (p2 +8)
7. 21 xy2 (3x – 2)
Solution:
21 xy2 (3x – 2) = 3 × 7 × x × y × y × (3x -2)
8. 121mn (m2 – n)
Solution:
121mn (m2 – n) = 11 × 11 × m × n × (m2 -n)
Question 3. Let us find the common factors of the following algebraic expressions :
1. 22xy, 33xz
Solution:
22xy, 33xz
Common factors = 11 , x, 11x
2. 14ab2 , 21ab
Solution:
14ab2 , 21ab
Common factors = 7, a, b, 7a, 7b, 7ab
3. – 16mnl, – 39nl2
Solution:
– 16mnl, – 39nl2
Common factors = – 1, – n, – 1, nl, – nl, n, I
4. 12a2b, 18ab2, 24abc
Solution:
12a2b, 18ab2, 24abc
Common factors = 2, 3, 6, a, b, 2a, 2b, 3a, 3b, 6a, 6b, ab, 2ab, 3ab, 6ab
5. 2xy, 4yz, 6xz
Solution:
2xy, 4yz, 6xz
Common factors = 2.
6. 18x2, 27x3, – 45x
Solution:
18x2, 27x3, – 45x
Common factors = 3, 9, x, 3x, 9x
7. 5mn, 6n2l2, 7l3m2
Solution:
5mn, 6n2l2, 7l3m2
Common factors = 1.
Question 4. Let us write two such algebraic e×pressions which have the following as their Common Factors
1. x2
Solution:
⇒ x2 = 3x2, 4x33y
2. 2xy
Solution:
2xy = 4x2y2q, 6xyq
3. 4a2
Solution:
4a2= 12a3y, 16a2x
4. (mn + 2)
Solution:
(mn + 2) = 5(mn + 2), 7(mn + 2)2
5. x (y + 2)
Solution:
x (y + 2) = 7x2(y + 2), 9x(p + q)(y + 2)
Question 5. Let us factorize the following
1. 5 + 10x
Solution:
5 + 10x = 5(1 +2x)
2. 2x – 6
Solution:
2x – 6 = 2(x – 3)
3. 7m – 14n
Solution:
7m – 14n = 7(m – 2n)
4. 18xy + 21 xz
Solution:
18xy + 21 xz = 3x(6y + 7z)
5. 4xy + 6yz
Soution:
4xy + 6yz = 2y(2x + 3z)
6. 7xyz – 6xy
Solution:
7xyz – 6xy = xy(7z – 6)
7. 7a2 + 14a
Solution:
7a2 + 14a = 7a(a + 2)
8. – 15m + 20
Solution:
– 15m + 20 = 5(- 3m + 4)
9. 6a2b + 8a2b
Solution:
6a2b + 8a2b = 2ab(3a + 4b)
10. 3a2 – ab2
Solution:
3a2 – ab2 = a (3a – b2)
11. abc – bcd =
Solution:
abc – bcd = bc(a – d)
12. 60xy3 – 4xy – 8
Solution:
60xy3 – 4xy – 8 = 4(15xy3 – xy – 2)
13. x2yz + xy2z + xyz2
Solution:
x2yz + xy2z + xyz2 = xyz(x + y + z)
14. a3 – a2 + a
Solution:
a3 – a2 + a = a(a2 – a + 1 )
15. x2y2z2 + x2y2 + x2y2q2
Solution:
x2y2z2 + x2y2 + x2y2q2 = x2y2(z2 +1 + q2)
Question 6. Let’s Factorise the following algebraic e×pressions
1. xy + 2x + y + 2
Solution :
Given
xy + 2x + y + 2
= x(y + 2) + 1(y + 2) = (y + 2)(× + 1)
xy + 2x + y + 2 = (y + 2)(× + 1)
2. ab – 5b + a – 5
Solution:
Given
ab – 5b + a – 5
= b(a – 5) + 1 (a – 5) = (a – 5)(b + 5)
ab – 5b + a – 5 = (a – 5)(b + 5)
3. 6xy – 9y + 4x – 6
Solution :
Given
6xy – 9y + 4× – 6
= 3y(2x – 3) + 2(2x – 3) = (2x – 3)(3y + 2)
6xy – 9y + 4× – 6 = (2x – 3)(3y + 2)
4. 15m + 9 – 35mn – 21 n
Solution :
Given
15m + 9 – 35mn – 21 n
= 3(5m + 3) – 7n(5m + 3) = (3 – 7n)(5m + 3)
15m + 9 – 35mn – 21 n = (3 – 7n) (5m + 3)
5. ax + bx – ay – by
Solution :
Given
ax + bx – ay – by
= x(a + b) – y(a + b) = (a +b)(x – y)
ax + bx – ay – by = (a +b)(x – y)
6. c – 9 + 9ab – abc
Solution :
Given
c – 9 + 9ab – abc
= – 1 (9 – c) + ab(9 – c) = (9 – c)(ab – 1)
c – 9 + 9ab – ABC = (9 – c)(ab – 1)
Class VII Math Solution WBBSE Factorization Exercise 6.4
Question 1. Let us factorize the following
1. x2 + 14× + 49
Solution :
Given
×2 + 14x + 49
= (x)2 + 2.x.7 + (7)2 = (x + 7)2 = (x + 7)(x+ 7)
×2 + 14x + 49 = (x + 7)(x+ 7)
2. 4m2 – 36m + 81
Solution :
Given
4m2 – 36m + 81
= (2m)2 – 2.2m.9 + (9)2
= (2m – 9)2 = (2m – 9)(2m – 9)
4m2 – 36m + 81=(2m – 9)(2m – 9)
3. 25 x2 + 30x + 9
Solution :
Given
25x2 + 30x + 9
= (5x)2 + 2.5 x .3 + (9)2 = (5x + 3)2 = (5x + 3) (5x + 3)
25x2 + 30x + 9 = (5x + 3) (5x + 3)
4. 121b2– 88bc + 16c2
Solution :
Given
121b2 – 88bc + 16c2
= (11b)2 – 2.11 b.4c + (4c)2 = (11 b – 4c)2
. = (11 b – 4c)(11 b – 4c)
121b2 – 88bc + 16c2 = (11 b – 4c)(11 b – 4c)
WBBSE Class 7 Math Solution
5. (xy)2 – 4x2y2
Solution :
Given
(x2y)2 – 4x2y2
= x2y2 – 4x2y2 = .x2y2(x2 – 4) = x2y2{(x)2 – (2)2}
= x2y2(x + 2)(x – 2) = x.x.y.y.(x + 2)(x – 2)
(x2y)2 – 4x2y2 = x.x.y.y.(x + 2)(x – 2)
6. a4 + 4a2b2 + 4b4
Solution :
Given
a4 + 4a2b2 + 4b4
= (a2)2 + 2.a2.2b2 + (2b)2
= (a2 + 2b2)
= (a2 + 2b2)(a2 + 2b2)
a4 + 4a2b2 + 4b4 = (a2 + 2b2)(a2 + 2b2)
7. 4x2 – 1 6
Solution:
Given
4x2-16
= 4(x2– 4) = 4{(x)2 – (2)2} = 2 × 2 × (x + 2)(x – 2)
4x2-16 = 2 × 2 × (x + 2)(x – 2)
8. 121 – 36x2
Solution :
Given
121 – 36x2
= (11)2 – (6x)2 = (11 + 6x)(11 – 6x)
121 – 36x2 = (11 + 6x)(11 – 6x)
9. x2y2 – p2q2
Solution :
Given
x2y2 – p2q2
= (xy)2 – (pq)2= (xy + pq)(xy – pq)
x2y2 – p2q2 = (xy + pq)(xy – pq)
10. 80m2 -125
Solution :
Given
80m2 -125
= 5(16m2 – 25) = 5{(4m)2 – (5)2} = 5(4m + 5)(4m – 5)
80m2 -125 = 5(4m + 5)(4m – 5)
11. ax2 – y2
Solution:
Given
ax2 – y2
= ax2 – ay2 = a{(x)2 – (y)2} = a (x + y)(x – y)
ax2 – y2 = a (x + y)(x – y)
12. I – (m + n)2
Solution :
Given
I – (m + n)2
= (I)2 – (m + n)2 = {I + (m + n)} {I – (m + n)}
= (I + m + n)(l – m – n)
I – (m + n)2 = (I + m + n)(l – m – n)
13. (2a – b – c)2 – (a – 2b – c)2
Solution :
Given
(2a – b – c)2 – (a – 2b – c)2
= {{2a – b – c) + (a – 2b – c)} {(2a – b – c) – (a – 2b – c)}
= (2a – b – c + a – 2b – c)(2a – b – c – a + 2b + c)
= (3a – 3b – 2c)(a + b)
(2a – b – c)2 – (a – 2b – c)2 = (3a – 3b – 2c)(a + b)
14. x2 – 2xy – 3y2
Solution :
Given
x2 – 2xy – 3y2
= x2 – (3 – 1 )xy – 3y2 = x2 – 3xy + xy – 3y2
= x(x – 3y) + y(x – 3y) = (x – 3y)(x + y)(xv)
x2 – 2xy – 3y2 = (x – 3y)(x + y)(xv)
15. x2+ 9y2 + 6xy – z2
Solution :
Given
x2+ 9y2 + 6xy – z2
= x + 6xy + 9y2 – z2
= (x)2 + 2.x.3y + (3y)2 – (z)2
= (x + 3y)2 – (z)2
= (x + 3y + z)(x + 3y – z)
x2+ 9y2 + 6xy – z2 = (x + 3y + z)(x + 3y – z)
16. a2 – b2 + 2bc – c2
Solution :
Given
a2 – b2 + 2bc – c2
= a2 – (b2 – 2bc + c2) = (a)2 – (b – c)2
= {a + (b – c)} {a – (b – c)} = (a + b – c)(a – b + c)
a2 – b2 + 2bc – c2 = (a + b – c)(a – b + c)
WBBSE Class 7 Math Solution
17. a2(b-c)2-b2(c-a)2
Solution :
Given
a2(b-c)2-b2(c-a)2
= {a (b – c)}2 – {b(c – a)}2 = (ab – ac)2 – (bc – ab)2
= {(ab – ac) + (bc – ab)} {(ab – ac) – (bc – ab)}
= (ab – ac + bc – ab) (ab – ac – be + ab)
= (bc – ac) (2ab – ac – bc)
= c(b – a) (2ab – bc – ca)
a2(b-c)2-b2(c-a)2 = c(b – a) (2ab – bc – ca)
18. x2 – y2 – 6yz – 9z2
Solution :
Given
x2 – y2 – 6yz – 9z2
= x2 – (y 2+ 6yz + 9z2)
= (x)2 – {(y)2 + 2.y.3z + (3z)2}
= (x)2 – (y + 3z)2
= (x + y + 3z) (x – y – 3z)
x2 – y2 – 6yz – 9z2 = (x + y + 3z) (x – y – 3z)
19. x2 – y2 + 4x – 4y
Solution :
Given
x2 – y2 + 4x – 4y
= {(x)2 -(y)} 2 + 4(x-y)
= (x + y)(x – y) + 4(x – y) = (x – y)(x + y + 4)
x2 – y2 + 4x – 4y = (x – y)(x + y + 4)
20. a2 -b2 + c2 – d2 – 2(ac – bd)
Solution :
Given
a2 -b2 + c2 – d2 – 2(ac – bd)
= a2 – b2+ c2 – d2 – 2ac + 2bd
= a2 – 2ac + c2 – b2 + 2bd – d2
= {(a)2 – 2,a.c + (c)2} – (b2 – 2bd + d2)
= (a – c)2 – (b – d)2
= {(a – c) + (b – d)} {(a – c) – (b – d)}
= (a – c + b – d) (a – c – b + d)
= (a + b – c – d) (a – b – c + d)
a2 -b2 + c2 – d2 – 2(ac – bd) = (a + b – c – d) (a – b – c + d)
21. 2ab – a2 – b2 + c2
Solution :
Given
2ab – a2 – b2 + c2
= c2 – a2 + 2ab – b2
= (c)2 – (a2 – 2ab + b2) = (c)2 – (a – b)2
= (c + a – b)(c – a + b) = (a – b + c)(b + c – a)
2ab – a2 – b2 + c2 = (a – b + c)(b + c – a)
22. 36x2 – 16a2 – 24ab – 9b2
Solution :
Given
36x2 – 16a2 – 24ab – 9b2
= 36x2 – (16a2 + 24ab + 9b2)
= 36x2 – {(4a)2 + 2.4a.3b + (3b)2}
= (6x2) – (4a + 3b)2
= {6x + (4a + 3b)} {6x – (4a + 3b)}
= (6x + 4a + 3b) (6x – 4a – 3b)
36x2 – 16a2 – 24ab – 9b2 = (6x + 4a + 3b) (6x – 4a – 3b)
23. a2 – 1 + 2b – b2
Solution :
Given
a2 – 1 + 2b – b2
= a2 – (1 – 2b + b)2
= (a)2 – (1 – b) = (a +1 – b) {a (1 b)}
= (a – b + 1 )(a + b – 1 )
a2 – 1 + 2b – b2 = (a – b + 1 )(a + b – 1 )
WBBSE Class 7 Math Solution
24. a2 – 2a – b2 + 2b
Solution :
Given
a2 – 2a – b2 + 2b
= a2 – b2 + 2b – 2a
= (a + b) (a – b) – 2(a – b)
= (a b)(a + b – 2)
a2 – 2a – b2 + 2b = (a b)(a + b – 2)
25. (a2 – b2)(c2 – d2– 4abcd)
Solution :
Given
(a2 – b2)(c2 – d2– 4abcd
(a2 – b2)(c2 – d2) – 4abcd
= a2c2 – b2c2– a2d2 + b2d2 – 4abcd
= a2c2 + b2d2 -.2abcd – a2d2– 2abcd – b2c2
= {(ac)2 – 2abcd + (bd)2} – {a2d2 + 2abcd + b2c2}
= (ac – bd)2 – (ad + bc)2
= {(ac – bd) + (ad + bc)} {(ac – bd) – (ad + bc)}
= (ac – bd + ad + bc) (ac – bd – ad – bc)
(a2 – b2)(c2 – d2– 4abcd = (ac – bd + ad + bc) (ac – bd – ad – bc)
26. a2 – b2 – 4ac + 4bc
Solution :
Given
a2 – b2 – 4ac + 4bc
= {(a)2 – (b)2} – 4c(a – b)
= (a + b) (a – b) – 4c(a – b) = (a – b)(a + b – 4c)
a2 – b2 – 4ac + 4bc = (a – b)(a + b – 4c)
27. a2 – b2 – c2+ d2)2 – 4(ad – bc)2
Solution:
Given
a2 – b2 – c2+ d2)2 – 4(ad – bc)2
= (a2 – b2 – c2+ d2)2 – {2(ad – bc)}2
= (a2 – b2 – c2 + d2 + 2ad – 2bc)
= {a2 + 2ad + d2– b2 – 2bc – c2}
= [{(a)2 + 2.a.d + (d)2} – {(b)2 + 2.b.c + (c)2}]
= {(a + d)2 – (b + c)2}
= {(a + d) + (b + c)} {(a + d) – (b + c)}
= (a + b + c + d) (a + d – b – c)
= (a + b + c + d)(a – b – c + d)
a2 – b2 – c2+ d2)2 – 4(ad – bc)2 = (a + b + c + d)(a – b – c + d)
28. 3x2 – y2 + z2 – 2xy – 4xz
Solution :
Given
3x2 – y2 + z2 – 2xy – 4xz
= 4x2 – x2 – y2 + z2 – 2xy – 4xz
= 4x2 – 4xz + z2 – x2 – 2xy – y2
= {(2x)2 – 2.2x.z + (z)2} – (x2 + 2xy + y2)
= (2x – z)2 – (x + y)2
= {(2x – z) + (x + y)} {(2x – z) – (x + y)}
= ( 2x – z + x + y) (2x – z – x – y)
= (3x + y – z) (x – y – z)
3x2 – y2 + z2 – 2xy – 4xz = (3x + y – z) (x – y – z)
WBBSE Class 7 Math Solution Question 2. Let us factorize the following
1. 81x4 + 4v4
Solution :
Given
81x4+ 4y4
(9x2)2 + (2y2)2 + 2.9x2.2y2 – 36x2y2
= (9x2 + 2y2)2 – (6xy)2
. = (9x2 + 2y2 + 6xy) (9x2 + 2y2 – 6xy)
= (9x2 + 6xy + 2y2) (9x2 – 6xy + 2y2)
81x4+ 4y4 = (9x2 + 6xy + 2y2) (9x2 – 6xy + 2y2)
2. p4 – 13p2q2 + 4q4
Solution :
Given
p4 – 13p2q2 + 4q4
= (p2)2 – 2.p2.2q2 + (2q2)2 -9p2q2
= (p2 – 2q2)2 – (3pq)2 = (p2 – 2q2 + 3pq) (p2– 2q2 – 3pq)
= (p2 + 3pq – 2q2) (q2 – 3pq – 2q2)
p4 – 13p2q2 + 4q4 = (p2 + 3pq – 2q2) (q2 – 3pq – 2q2)
3. x8 – 16y8
Solution :
Given
x8 – 16y8
= (x4)2 – (4y4)2
= (x4 + 4y4) (x4 – 4y4)
= {(x2)2 + 2.x2.2y2 + (2y2)2 – 4x2y2} {(x2)2 – (2y)2}
= {(x2 + 2y2)2 – (2xy)2} (x2 + 2y2) (x2 – 2y2)
= (x2 + 2y2 + 2xy) (x2 + 2y2 – 2xy) (x2 + 2y2) (x2 – 2y2)
= (x2 + 2xy + 2y2) (x2 2xy + 2y2) (x2 + 2y2) (x2 – 2y2)
x8 – 16y8= (x2 + 2xy + 2y2) (x2 2xy + 2y2) (x2 + 2y2) (x2 – 2y2)
4. x4 + x2y2 + y4
Solution :
Given
x4 + x2y2 + y4
= (x2)2 + 2x2y2 + (y2)2 – x2y2
= (x2+ y2)2 – (xy)2
= (x2 + y2 + xy) (x2 + y2 – xy)
= (x2 + xy + y2) (x2 – xy + y2)
x4 + x2y2 + y4 = (x2 + xy + y2) (x2 – xy + y2)
5. 3x4 + 2x2y2 – y4
Solution:
Given
3x4 + 2x2y2– y4
= 3x4 + 3x2y2 – x2y2 – y4
= 3x2(x2 + y2) – y2(x2 + y2)
= (x2 + y2) (3x2 – y2)
3x4 + 2x2y2– y4 = (x2 + y2) (3x2 – y2)
6. x4 + x2 + 1
Solution :
Given
x4 + x2 + 1
= (x2)2 + 2.x2.1 +(1)2-x2
= (x2 + 1 )2 – (x)2 = (x2 + 1 +x) (x2 + 1 – x)
= (x2 + x + 1 ) (x2 – x + 1 )
x4 + x2 + 1 = (x2 + x + 1 ) (x2 – x + 1 )
7. x4 + 6x2y2 + 8y4
Solution:
Given
x4 + 6x2y2 + 8y4
= x4 + 4x2y2 + 2x2y2 + 8y2
= x2(x2 + 4y2) + 2y2(x2 + 4y2)
= (x2 + 4y2)(x2 + 2y2)
x4 + 6x2y2 + 8y4 = (x2 + 4y2)(x2 + 2y2)
WBBSE Class 7 Math Solution 8. 3x2 – y2 + z2 – 2xy – 4xz
Solution :
Given
3x2 – y2 + z2 – 2xy – 4xz
= 4x2 – x2 – y2 + z2 – 2xy – 4xz
= 4x2 – x2 – y2 + z2 – 2xy – 4xz
= 4x2 – 4xz + z2 – x2 – 2xy – y2
= (4x2 – 4xz + z2) – (x2 + 2xy + y2)
= {(2x)2 – 2. 2x.z + z)2} – {(x)2 + 2.x.y + (y)2}
= (2x – z)2 – (x + y)2
= {(2x – z) + (x + y)} {(2x – z) – (x + y)
= (2x – z + x + y) (2x – z – x – y)
= (3x + y – z) (x – y – z)
3x2 – y2 + z2 – 2xy – 4xz = (3x + y – z) (x – y – z)
9. 3x4 – 4x2y2 + y4
Solution :
Given
= 3x4 – 3x2y2– x2y2 + y4
= 3x2(x2 – y2) – y2(x2 – y2)
= (x2 – y2) (3x2 – y2)
= {(x)2 -(y)2} (3x2 – y2)
= (x + y) (x – y) (3x2 – y2)
3x4 – 3x2y2– x2y2 + y4 = (x + y) (x – y) (3x2 – y2)
10. p4 – 2p2q2 – 15q2
Solution :
Given
p4 – 2p2q2 – 15q2
= p4 – (5 – 3)p2q2 – 15q5
= p4 – 5p2 q2 + 3p2q2 – 15q2
= P2(P2 5q2) + 3q2(p2 + 3q2)
= (p2 – 5q2) (p2 + 3q2)
p4 – 2p2q2 – 15q2 = (p2 – 5q2) (p2 + 3q2)
11. x8 + x4y4 + y8
Solution :
Given
x8 + x4y4 + y8
= x8 + 2x4y4 + y8 – x4y4
= {(x4)2 + 2x4y4 + y4 + (y4)4} – (x4y4)4
= (x4 + y4)4 – (x4y4)4
= (x4 + y4 + x2y2) (x2 + y4 – x2y2)
= {x4 + 2x2y2 + y4 – x2y2} (x4 + y4 – x2y2)
= {(x2)2 + 2x2y2 + (y2)2 – (xy)2} (x4 + y4 – x2y2)
= {(x2 + y2) – (xy)2} (x4 + y4 – x2y2)
= (x2 + y2 + xy) (x2 + y2– xy) (x4 + y4 – x2y2)
x8 + x4y4 + y8 = (x2 + y2 + xy) (x2 + y2– xy) (x4 + y4 – x2y2)